A Healthy Balance of Homeostasis by Epigenetic Regulator SIRT1 May Prevent the Development of a Specific "Soil" that Supports Metabolic Disorders and Related Cancers - Nemeth, Zsuzsanna; Kiss, Eva; Takacs, Istvan (Current Overview on Disease and Health Research Vol. 4, 2022)
SIRT1 was discovered in 1979, but increased interest in this protein did not come until 20 years later, when its overexpression was reported to extend the lifespan of yeast. Since then, several studies have shown the benefits of its increased expression in preventing or delaying of many diseases. As a histone deacetylase, SIRT1 is an epigenetic regulator but has several non-histone targets involved in metabolism, energy sensing pathways, circadian machinery, and inflammatory regulation. Disturbances in these interconnected processes cause different diseases, however they seem to have a common root in the imbalance of inflammatory processes and lower levels or inactivation of SIRT1. SIRT1 inactivation has also been implicated in the severity of COVID-19, and its low level has been considered a predictor of uncontrolled COVID-19. Several other diseases, such as metabolic disease, obesity, diabetes, Alzheimer's disease, cardiovascular disease or depression, are associated with chronic inflammation and similarly show reduced SIRT1 level. It has recently become known that SIRT1 can be inducible by calorie restriction/proper nutrition, physical activity and appropriate emotional state. Indeed, a healthier metabolic state is associated with higher levels of SIRT1 expression. These suggest that a suitable lifestyle as a non-pharmacological treatment may be a beneficial tool in the prevention of inflammation or metabolic disturbance-related diseases, and in medical practice it can be part of the complementary therapy to achieve better therapeutic response and quality of life. In this review we aimed to link the beneficial effects of SIRT1 to diseases in which its levels are reduced. In addition, we sought to collect evidence for interventions or treatments that increase SIRT1 expression, thereby open the possibility of using them as preventive or complementary therapy in medical practice.